2008
DOI: 10.1095/biolreprod.107.066050
|View full text |Cite
|
Sign up to set email alerts
|

Sex of Bovine Embryos May Be Related to Mothers' Preovulatory Follicular Testosterone1

Abstract: Although the sex of the offspring in mammals is commonly viewed as a matter of chance (depending on whether an X or a Y chromosome-bearing spermatozoon reaches the ovum first), evolutionary biologists have shown that offspring sex ratios are often significantly related to maternal dominance, a characteristic that has been shown to be linked to testosterone in female mammals, including humans. Hence, we hypothesized that variations in female testosterone might be related to reproductive mechanisms associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 42 publications
3
56
3
2
Order By: Relevance
“…While many studies have focused on how mammalian females could influence the sex of the offspring both before and after conception (Hardy, 1997;Grant et al, 2008;Grant and Chamley, 2010), there is little understanding of how offspring sex can affect metabolism in dairy cows during the transition period. Fetal hormones may provide a means for understanding the influence of offspring sex on maternal metabolism during the early transition period, especially since they can readily diffuse into maternal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have focused on how mammalian females could influence the sex of the offspring both before and after conception (Hardy, 1997;Grant et al, 2008;Grant and Chamley, 2010), there is little understanding of how offspring sex can affect metabolism in dairy cows during the transition period. Fetal hormones may provide a means for understanding the influence of offspring sex on maternal metabolism during the early transition period, especially since they can readily diffuse into maternal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the level of testosterone in bovine follicular fluid (FF) may predispose the ovulated oocyte to be preferentially fertilized by either an X-or a Y-chromosome-bearing spermatozoa [10]. In support of this theory, a positive correlation has been described between the concentration of testosterone in follicular fluid and the likelihood of the oocyte recovered from that follicle being fertilized in vitro by a Y-bearing spermatozoa [11]. If this notion is true, then no matter how technically successful sperm sorting techniques are, fertility rates will be low.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies seem to reveal that local resource competition among the philopatric sex is the most important selective force affecting birth sex ratios (Hiraiwahasegawa 1993, Hjernquist et al 2009). Our understanding of this issue is still greatly hampered by the lack of exact knowledge about male reproductive success and the proximate mechanisms responsible for the variations in sex ratios (Hard et al 2006, Mari et al 2008, although several recent studies have investigated the proximate mechanisms responsible for sex-ratio variations (Grant et al 2008, James 1996, Cameron et al 2008, Goerlich et al 2009, Helle et al 2008, Cameron 2004, Love et al 2005, Mari et al 2008. Environmental conditions that predict lower survival of males may lead to female-biased sex ratios the following year (Monard et al 1997).…”
mentioning
confidence: 99%